2022
DOI: 10.1108/k-01-2022-0137
|View full text |Cite
|
Sign up to set email alerts
|

An extended MABAC method for multiple-attribute group decision making under probabilistic T-spherical hesitant fuzzy environment

Abstract: PurposeThe purpose of this article is to present the idea of a T-spherical hesitant fuzzy set associated with probability and to develop an extended multi-attributive border approximation area comparison (MABAC) method under probabilistic T-spherical hesitant fuzzy (Pt-SHF) settings.Design/methodology/approachThe authors define some basic operational laws for Pt-SHF sets (Pt-SHFSs) and a comparison method of two probabilistic T-spherical hesitant fuzzy numbers (Pt-SHFNs) is proposed. Moreover, some Pt-SHF aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Debnath et al 57 In 59 , T-SF Power Muirhead mean operator-based MAGDM is established to tackle the decision problem of daily life. Researchers who are interested are directed to some decent literature on MAGDM using T-SFSs [60][61][62][63] .…”
Section: Fuzzy Multiple-attribute Group Decision-makingmentioning
confidence: 99%
“…Debnath et al 57 In 59 , T-SF Power Muirhead mean operator-based MAGDM is established to tackle the decision problem of daily life. Researchers who are interested are directed to some decent literature on MAGDM using T-SFSs [60][61][62][63] .…”
Section: Fuzzy Multiple-attribute Group Decision-makingmentioning
confidence: 99%
“…It is based on the distance of evaluation matrix obtained from each decision maker to the border approximation area matrix. Numerous studies based on application of MABAC method to decision making theory are available in the literature (Java et al, 2022;Jiang et al, 2022;Su et al, 2022;Liu and Wang, 2022;Gurmani et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen et al (2021) unfolded generalized and group-generalized T-SF geometric aggregation operations (including (ordered) weighted and hybrid geometric operations) to support multiple-criteria assessments. Next, in the circumstances of probabilistic T-spherical hesitant ambiguity, Gurmani et al (2022) initiated aggregation operators and advanced an extended approach for boundary approximation region comparison in treating group decision issues. In intervalvalued T-SF circumstances, Hussain et al (2022a) utilized Frank aggregation operators to propose a method of assessing business proposals.…”
Section: T-sf Theory In Uncertain Decision Contextsmentioning
confidence: 99%
“…In particular, based on Table 1, it can be easily observed that many researchers discussed the modularization of multiple-criteria choice methods in the context of T-SF sets with aggregation operations or averaging (i.e. mean) operations, such as Akram and Martino (2022), Al-Quran (2021), Chen et al (2021), Gurmani et al (2022), Hussain et al (2022aHussain et al ( , 2022b, Karaaslan and Al-Husseinawi (2022), Khan et al (2022), Liu et al (2021c), Mahnaz et al (2022), Wang (2021), Wang and Zhang (2022), Yang and Pang (2022), Yang et al (2021), Zedam et al (2022), andZeng et al (2021). That is, many of the above works of literature focus on models of aggregating or averaging operations, which belong to a measurement of the central tendency of a finite set of T-SF information.…”
Section: T-sf Theory In Uncertain Decision Contextsmentioning
confidence: 99%